Cultural Representation Analysis in English Textbook in Indonesia EFL Secondary School Students - Handayani, Rita; Yunita, Della (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2025)
This study aims to examine the representation of cultural dimensions in pictures and written texts (students’ exercises and reading texts) in the English textbook Work in Progress (2022), based on Yuen’s (2011) and Chao’s (2011) theories, and to determine whether the cultural dimensions in the textbook align with intercultural competencies and the Pancasila Student Profile in the Merdeka curriculum. Cultural dimensions are crucial in language learning as they foster global awareness, intercultural understanding, and appreciation of cultural diversity. This qualitative study employs a content analysis methodology to analyze data from the English textbook Work in Progress (2022), designed for tenth-grade high school students and published by the Ministry of Education and Culture of the Republic of Indonesia. The analysis, based on Yuen’s (2011) cultural dimensions, indicates that perspectives are the most dominant dimension, followed by persons, products, and practices. Furthermore, the cultural categories based on Chao’s (2011) theory are dominated by international culture, intercultural interaction, source culture, target culture, and universality across culture. The findings highlight the textbook’s alignment with the Merdeka Curriculum’s goals of promoting intercultural competence and global diversity. Yuen’s (2011) cultural dimensions (persons, perspectives, products, and practices) and Chao’s (2011) cultural categories (international culture, intercultural interaction, source culture, target culture, and universality across culture) reflect the Merdeka Curriculum’s emphasis on understanding how cultural dimensions in textbooks support the Pancasila Student Profile’s goal of recognizing and appreciating cultural diversity.